“INTEGRATING COMICS AS AN INSTRUCTIONAL TOOL IN TEACHING TRANSLATED ASIAN LITERARY WORKS: ITS INFLUENCE ON STUDENTS’ ACADEMIC LEARNING IN FILIPINO” - SAMAMA, SARAH (International Journal of Arts, Sciences and Education, 2025)
This research aims to examine the effectiveness of using comics as a supplementary teaching tool in teaching Asian Literature to Grade 9 students at Salabaca National High School. Using an experimental design, two groups of students were compared: an experimental group that used comics and a control group that utilized traditional teaching methods. The study employed complete enumeration in selecting the respondents. Data were gathered through a test evaluated by five Filipino language experts in accordance with DepEd Order No. 001, s. 2021. The results were analyzed using statistical methods to determine the impact of comics on student learning. The findings revealed that the experimental group demonstrated higher levels of comprehension and participation compared to the control group. This indicates that the use of comics can be an effective strategy in literature instruction, as it facilitates understanding and provides a more interactive learning experience. This study supports the use of visual media in education, particularly in the Filipino subject. Comics help simplify complex concepts and engage students in the learning process, making lessons more dynamic and accessible.